Universal Methods for Transgene Induction Using the Dexamethasone‐Inducible Transcription Activation System pOp6/LhGR in Arabidopsis and Other Plant Species. Issue 2 (12th March 2019) - Samalova, Marketa; Kirchhelle, Charlotte; Moore, Ian
Abstract: Use of chemically inducible systems for transgene expression is a crucial requirement for modern plant biology research, as it allows (1) expression of transgenes that compromise plant viability or fertility when constitutively expressed and (2) spatiotemporal control of transgene expression levels. We describe the stringently regulated and highly responsive dexamethasone‐inducible gene expression system pOp6/LhGR, which comprises the chimeric transcription activator LhGR and the corresponding pOp6 promoter. Upon induction, the LhGR activator binds to the pOp6 promoter and induces expression of the target gene of interest. We provide detailed protocols for inducing transgene expression at different developmental stages and in different plant species and discuss dexamethasone stability and use of its analogs. We also introduce new, versatile, GATEWAY‐compatible binary vectors that are now available for the pOp6/LhGR system. © 2019 by John Wiley & Sons, Inc.